Convergence of Variational Iteration Method for Fractional Delay Integrodifferential-Algebraic Equations. (16th May 2017) - Fu, Yayun; Liu, Hongliang; Xiao, Aiguo
Abstract : Fractional order delay integrodifferential-algebraic equations are often used for many practical modeling problems in science and engineering, which have time lag, memory, constraint limit, and so forth. These yield some difficulties in numerical computation. The iterative methods are good choice. In the present paper, we construct variational iteration method for solving them by using the appropriate restricted variation. This overcomes the difficulties caused by limitations of large storage amount and algebraic constraint and extends the previous conclusions.